Chaihu-Longgu-Muli decoction improves sleep disorders by restoring orexin-A function in CKD mice - Cao, Xin-li; Peng, Xue-mei; Li, Gong-bo; Ding, Wei-sen; Wang, Kai-zhen; Wang, Xiao-lei; Xiong, Yan-ying; Xiong, Wei-jian; Li, Fan; Song, Min (Frontiers in Endocrinology, 2023)
Chaihu-Longgu-Muli decoction (CLMD) is a well-used ancient formula originally recorded in the “Treatise on Febrile Diseases” written by the founding theorist of Traditional Chinese Medicine, Doctor Zhang Zhongjing. While it has been used extensively as a therapeutic treatment for neuropsychiatric disorders, such as insomnia, anxiety, and dementia, its mechanisms remain unclear. In order to analyze the therapeutic mechanism of CLMD in chronic renal failure and insomnia, An adenine diet-induced chronic kidney disease (CKD) model was established in mice. Furthermore, we analyzed the impact of CLMD on sleep behavior and cognitive function in CKD mice, as well as the production of insomnia related regulatory proteins and inflammatory factors. Finally, we found CLMD improved sleep and cognitive levels in CKD mice. The mechanism may be related to the up-regulation of Orexin-A and increased phosphorylation level of Calcium/Calmodulin Dependent Protein Kinase Kinase (CaMKK)2/Adenosine 5’-monophosphate (AMP)-activated protein kinase (AMPK), which further inhibits Nuclear factor kappa-B(NF-κB) downstream signaling pathways, thereby improving the disordered inflammatory state in the central and peripheral system without affecting renal function.